Injection-Less Conductance Method for Vascular Sizing - Dabiri, Ali E.; Kassab, Ghassan S. (Frontiers in Physiology, 2018)
Lumen vessel sizing is important for optimization of interventional outcomes for treatment of vascular disease. The objective of this study is to develop an injection-less method to determine the lumen diameter, using multiple frequencies that eliminates the need for saline injections. We utilize the same electrical conductance devices developed for the two-injection method. A mathematical electrical model was devised to estimate the lumen area and diameter of the arteries. In vitro experiments were used to validate the method for various lumen diameters with both 5-5-5 (peripheral) and 2-2-2 (coronary) spacing conductance guidewires. The majority of 11 vessel data fall within one standard deviation and all the data fall within two standard deviations. The results indicate that the two-frequency model can reasonably predict the lumen diameter in an in-vitro test set-up. Our findings show that this approach can potentially translate to in vivo which would enable pull-back to reconstruct the lumen area profile of the vessel.